PENGARUH KEPEMILIKAN INSTITUSIONAL TERHADAP KINERJA PERUSAHAAN NON-KEUANGAN YANG TERDAFTAR DI BEI PERIODE 2017-2020 - Cindy Melia Farahdiba; Ernie Hendrawaty (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study aims to analyze the effect of institutional ownership on company performance This study uses company performance as the dependent variable and independent variables such as foreign institutional ownership, state institutional ownership, and private institutional ownership. The sample of this study is non-financial companies listed on the Indonesia Stock Exchange in the period 2017 - 2020 with 82 companies and using the slovin formula. The data used in this study are 328 observational data. The analysis used in this research is multiple regression analysis with a panel data approach. The results of this study indicate that state institutional ownership has a negative effect on company performance because the main goal achieved is usually a political goal to maximize its own profits compared to the company. Meanwhile, foreign institutional ownership and private institutional ownership do not show a significant effect on company performance in the non-financial sector in Indonesia